Quality Choice and Product Differentiation in Monopoly Theory: An Application to the Puritan Church - Mixon, Franklin G. (Journal for the scientific study of religion, 2018)
French engineer and transport economist Jules Dupuit (1804-1866) conjectured more than 150 years ago that, in the context of a three-part tariff concerning French railroads, a discriminating monopolist will find it most profitable to distort product (service) quality at each of the two ends of the quality spectrum in order to prevent consumers in the middle class (i.e., the second of three classes) from defecting to either end (i.e., first or third class). This study extends a branch of the literature on the economics of religion by arguing that 17th-century Puritan theologians in colonial America used, in a way that is consistent with Dupuit's insights, Puritan religious doctrines related to eternal salvation and witchcraft to distort the quality, at both ends of the quality spectrum in a three-part tariff construct, of the religious services they provided to their parishioners. In doing so, we employ economic modeling from seminal studies of the medieval Roman Catholic Church.